2023
DOI: 10.3390/ijms24044124
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Genetic Relationship between Atherosclerosis and Non-Alcoholic Fatty Liver Disease through Biological Interaction Networks

Abstract: Non-alcoholic fatty liver disease (NAFLD) seems to have some molecular links with atherosclerosis (ATH); however, the molecular pathways which connect both pathologies remain unexplored to date. The identification of common factors is of great interest to explore some therapeutic strategies to improve the outcomes for those affected patients. Differentially expressed genes (DEGs) for NAFLD and ATH were extracted from the GSE89632 and GSE100927 datasets, and common up- and downregulated DEGs were identified. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…Together with PPARγ, CEBPA regulates the adipogenesis process and is involved in the sequence expression of adipocytespecific proteins [30][31][32][33][34][35][36]. CEBPA is upregulated in unstable plaques, and overexpression of CEBPA may contribute to the occurrence and development of atherosclerosis [37,38]. However, Bristol et al [39] observed that CEBPA and CEBPB bind the TNFR1 promoter, increase its expression through a positive feedback mechanism, and induce an increase in TNF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Together with PPARγ, CEBPA regulates the adipogenesis process and is involved in the sequence expression of adipocytespecific proteins [30][31][32][33][34][35][36]. CEBPA is upregulated in unstable plaques, and overexpression of CEBPA may contribute to the occurrence and development of atherosclerosis [37,38]. However, Bristol et al [39] observed that CEBPA and CEBPB bind the TNFR1 promoter, increase its expression through a positive feedback mechanism, and induce an increase in TNF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Il-1β and Il-6 are two important pro-inflammatory cytokines that amplify inflammation and sensitize hepatocytes to TNF-induced liver damage [43]. ADAMTS1, a metalloproteinase belonging to the ADAMS family, is involved in extracellular matrix (ECM) remodeling [44]. Several studies suggest a link between ADAMTS1 not only with the development of atherosclerotic plaques and ATH [45] but also with the ability to activate hepatic fibrotic TGF-b [46].…”
Section: Discussionmentioning
confidence: 99%
“…Pie charts were used to compare the proportions of elements, and to visualise their percentages (Figure 2). Elements such as 44 Ca, potassium ( 39 K), sodium ( 23 Na), 31 P, magnesium ( 24 Mg), zinc ( 66 Zn), and 56 Fe, which were present in the highest concentration, were removed from the graph to show the proportions of trace elements in the tissues examined. The series for both organs was split at 140 ppb.…”
Section: Mineral Status Of the Investigated Tissues Based On Icp-ms M...mentioning
confidence: 99%
“…A key role in the initiation of ATH is played by damage to the arterial endothelial cells by reactive oxygen and nitrogen species (ROS and RNS). These are generated by mitochondrial dysfunction in fatty hepatocytes and the vascular smooth muscle cell (VSMC) proliferation, induced by an overexpression of the coagulation factors angiotensin II [44,45], FII, FX, and FXII [46][47][48], and the production of pro-inflammatory IL-1β and TNF-α, under the influence of ox-LDL, as a consequence of atherogenic dyslipidaemia. Smaller, denser particles, sdLDLs, formed from very low-density lipoproteins (VLDLs), are also involved in the formation of atherogenic plaques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation